La práctica pedagógica en la formación del licenciado en educación básica: fortalezas y debilidades (2020)
This article aims to provide information about the contexts and scenarios where the Pedagogical Investigative Practice of Deepening is carried out, the strengths and weaknesses of the teachers in training in the first semester of 2018, the previous ones result of the analysis and preparation of the semi-annual technical report of the practice, which includes statistical information from the regional centers of distance education CREAD, in reference to municipalities where the practice is carried out gender, form of admission to the program among others. Therefore, the article has the function of visualizing the development of the PPIP, as the process in which the teachers in training have the possibility of demonstrating their strengths through the daily work with students in the academic, social aspects, and in which make the teacher which goes beyond being in a classroom to teach theories, models among others and visualize new contexts that sometimes teachers in training do not expect.